2014
DOI: 10.1149/2.0441414jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aluminum Doped Lithium-Manganese Rich Composites for Higher Rate Lithium-Ion Cathodes

Abstract: The effect of synthesis method and aluminum doping on layered lithium-manganese rich, mixed metal oxides is presented. Coprecipitation and sol-gel synthesized lithium-manganese rich composite materials revealed differences in capacity and cycle life, which appears from X-ray photoelectron spectra to be strongly related to the particles' surface reactivity. Small amounts of aluminum doping to the sol-gel material were shown to improve the rate capability and cyclability, in addition to decreasing voltage fade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…It is a daunting challenge for people to conquer the above mentioned problems of the Li-rich layered oxides to keep pace with the rapidly increasing requirement for satisfying batteries. Recently, people have made great efforts including cation and anion doping [10,12,13], surface modification [9,11,[14][15][16][17][18][19][20][21], innovation of synthesis method [22,23], and fabrication of nano-sized particles [6,24,25], to achieve the goal of commercialization of the Li-rich layered cathode materials. In particular, the surface modification by coating some materials such as metal oxides [15][16][17], phosphates [18][19][20], fluorides [9,11,21] has been regarded as one of the most effective measures to overcome drawbacks of Li-rich layered oxides.…”
Section: Introductionmentioning
confidence: 99%
“…It is a daunting challenge for people to conquer the above mentioned problems of the Li-rich layered oxides to keep pace with the rapidly increasing requirement for satisfying batteries. Recently, people have made great efforts including cation and anion doping [10,12,13], surface modification [9,11,[14][15][16][17][18][19][20][21], innovation of synthesis method [22,23], and fabrication of nano-sized particles [6,24,25], to achieve the goal of commercialization of the Li-rich layered cathode materials. In particular, the surface modification by coating some materials such as metal oxides [15][16][17], phosphates [18][19][20], fluorides [9,11,21] has been regarded as one of the most effective measures to overcome drawbacks of Li-rich layered oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the lithium-rich material has poor rate performance and low discharge voltage plateaus during cycling, especially under high temperature [137,138]. Metal ion doping exerts an enormous function on improving the electrochemical performance of these cathode materials [139][140][141] , etc. [147][148][149][150][151][152] can facilitate the diffusion of Li ions in the material.…”
Section: Al(iii) Doped Compositesmentioning
confidence: 99%
“…One of these alternatives are the metal air batteries which in the last years are under attention due to their high energy density and capacity on load and temperature [1,2]. Based on the latter, aluminum-based alloys as air battery doped with some metal ions had been reported by different authors with metals such as Al 3+, Mg 2+ , Ti 4+ , Cr 3+ , Zn 2+ , Co 3+ , Ga 3+ , and Ti 4+ [3][4][5], due mainly to their electrical and chemical properties, as well as to their low-cost acquisition compared with other metals like lithium and zinc [4]. Some authors had reported that the major problems that this kind of batteries present are their high corrosion rate and their high hydrogen evolution when in contact with the electrolyte conducing to a low anodic efficiency [6] Electrochemical techniques such as polarization curves, cyclic voltammetry, and electrochemical impedance spectroscopy had been employed to evaluate its properties with the aim to improve its physical and chemical features [7,8].…”
Section: Introductionmentioning
confidence: 99%